Research for Practice: Edge Computing. - MOR, NITESH (Communications of the ACM, 2019)
The author discusses the concept of edge computing which brings computing closer to the sources of data. He mentions its relation to cloud computing and the Internet of Things, its use in named data networking, and the potential applications for such computing as well as the need for further research.